A review of pre-Hispanic dental decoration in Colombia and report of two new cases (Bulletin of the International Association for Paleodontology, 2023)
A review of the subject in Colombia and two new cases are reported for this country. A comparison is made of the cases found in Colombia with others of the E1 type in Mesoamerica in times close to the year 1000 BP. The origin of this cultural practice in the region is discussed and it is concluded as a result of contacts with groups from the near Atlantic and Pacific coasts in earlier times.